RNAi screen for proteasome and cytoskeletal proteins affecting dendrite remodeling during drosophila metamorphosis. - Tan, Chyi Lin. (2009)
During Drosophila metamorphosis, the nervous system undergoes extensive remodeling as the fly transitions from the larval to adult stage. In the peripheral nervous system, several sensory neurons are removed by apoptosis, while some survive and remodel to become part of the adult sensory system. These neurons undergo extensive dendrite pruning and re-growth in order to form adult dendritic arbor. In this study, a RNA-mediated gene interference (RNAi) screen was performed to investigate the involvement of proteasome and cytoskeletal proteins plays in dendrite pruning process. Live confocal imaging was employed to visualize the dorsal dendritic arborization neurons carrying the GAL4 driver expressing UAS-GFP and RNAi constructs. Proteasome is found to be required in the dendrite pruning process that showed dendrite pruning defects at 18 hr APF. Immunostaining of ecdysone receptor (EcR) showed that the expression of receptor in the nucleus was not affected. This indicates that the proteasome is involved in downstream event of EcR signaling during dendrite remodeling. The RNAi of a motor protein (Unc-104) showed abnormal dendrite morphology and pruning defect at white pupa stage and 18 hr APF respectively. This may imply that the gene is involved in the dendritic arbor development and pruning process.